Simultaneous Estimation of Atorvastatin Calcium and Fenofibrate in Rabbit Plasma by RP-HPLC - D. Bhinge, Somnath; M. Malipatil, Sharangauda; Jondhale, Abhijeet; S. Savali, Anil (Asian Journal of Chemistry, 2012)
An accurate, rapid and simple reversed-phase high performance liquid chromatography (RP-HPLC) method was developed and validated for simultaneous estimation of atorvastatin calcium and fenofibrate in rabbit plasma. Plasma samples were treated with acetonitrile to precipitate proteins. Chromatographic separation was accomplished using CAPCELL PAK C8 (4.6 mm × 250 mm, 5 mm) analytical column with a mobile phase consisting of phosphate buffer and acetonitrile (28:72). Detection and quantification were performed by UV/VIS detection at 260 nm. The lower limits of detection and quantification were 0.05 μg mL-1 and 0.20 μg mL-1 for atorvastatin calcium and 0.07 μg mL-1 and 0.35 μg mL-1 for fenofibrate respectively. The calibration curves are linear over the concentration range 1 to 40 μg mL-1 for both atorvastatin and fenofibrate in rabbit plasma. The method was quantitatively evaluated in terms of linearity, precision, accuracy, recovery, selectivity and stability. The proposed method is simple, convenient and suitable for the analysis of atorvastatin calcium and fenofibrate in rabbit plasma.